Pengaruh Pelayanan Sistem Online Dan Promosi Terhadap Keputusan Pembelian Tiket Kereta Api Ekonomi (Study Kasus Pada Penumpang Kereta Api Ekonomi Di Stasiun Lahat) - Markus (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
This study aims to determine the effect of online system services and promotion on the decision to purchase an economic train ticket at the Lahat train station. The total sample is 100 respondents. Data obtained from questions using a questionnaire. Respondents' answers were then analyzed by multiple linear regression using the SPSS (Statistical Package for Social Science) analysis tool version 22 for 32-bit windows. Based on the analysis conducted, online system services and promotions have a significant effect on purchasing decisions with a regression coefficient Y = 22,273 + 0.122 X1 + 0.373 X2, which means that if the online system service and promotion variables do not exist or are equal to zero (0), the purchase decision is 22,273. . In the T test, the results show that the online system service variable has no significant effect on the economic train ticket purchase decision at Lahat train station and promotion has a significant effect on the economic train ticket purchase decision at the Lahat station. for economic train tickets in the South Sumatra region.